Pathos in the Poetry of COVID-19 Pandemic - Pokhrel, Mira (Koshi Pravah: Multidisciplinary Peer Reviewed Journal, 2022)
Poetry written during global pandemic of COVID-19 display pathos. The present article explores the use of pathos in four of the pandemic time poems. The study aims to unveil the predicament that the earth and humans endured during that time. For the analysis, theory of pathos has been taken as a tool. Pathos is one of the persuasive techniques that evokes the emotion of pity and sympathy to the audience or the readership on the suffering and sadness of the characters and the speakers of the rhetoric. This article also discusses vivid pictures of the pathetic state of the characters in the poems that is similar to the state of the entire humans who underwent it during pandemic. The present inquiry concludes that the poetry written during pandemic evokes the strong positive emotion of joy, excitement and hope, and the negative emotion of fear, sadness, agony and sympathy as well in the mind of the readers. Doing so, it establishes the close connection between the readership and the poets who had the same emotions and feelings of hope and excitement, and pain and sufferings during the composition of the poems.